The Impact of Leadership Technique, Ability and Personal-Professional Balance on the Performance of Workers at Star Wedding Organizer Kediri - TAMARA, KRISTINA YOSI (Universitas Nusantara PGRI Kediri, 2025)
Research aim : The purpose of this study is to find out The Influence of Leadership Style, Competence and Work-Life Balance on the Performance of Star Wedding Organizer Kediri Employees Design/Methode/Approach: The research uses a Causal Qualitative approach with a case study on Star Wedding Organizer Kediri employees. The data collection method is carried out through the distribution of questionnaires or questionnaires. The sample taken was as many as 45 people, all of whom were employees of Star Wedding Organizer Kediri. Data processing was carried out using IBM SPSS Statistics 25 by conducting a Classical Assumption Test which included the Normality Test, Multicollinearity Test, Heteroscedasticity Test and Autoceleration Test. In addition, Multiple Linear Regression Tests and Hypothesis Tests were also carried out in the form of Simultaneous Tests (Test f) and Partial Tests (Test t) as well as Determination Coefficient Tests Research Finding: from this study, it was concluded that the Leadership Style Variable (X1) and Work Life Balance (X3) did not have a significant effect on Employee Performance (Y). while the Competency Variable (X2) had a significant influence on Employee Performance (Y). then it was found that the current variable of 64.9% had no influence, so it can be interpreted that there are still variations of other factors that are not studied in this study, namely 35,1%. Theoretical contribution/Originality: This study makes a significant theoretical contribution and strengthens the literature on the findings of the influence of independent variables on dependent variables Practitionel/Policy implication: In practice, this study provides a solution to identify what causes affect employee performance Research limitation: the variables currently used do not have an influence on employee performance of 64.9% so there are still several variations of other variables that are not studied in this study, which is 35.1% so further research is needed